ANALISIS PERSEBARAN PENGGUNAAN LAHAN PERMUKIMAN BERDASARKAN ZONA RUANG DI KECAMATAN NGEMPLAK DAN KESESUAIANNYA DENGAN RDTR SLEMAN TIMUR - Putri Adiwibowo, Nadifa Aulia; Muta’ali, Lutfi (Jurnal Spasial, 2025)
The demand for land is a fundamental necessity that continues to change in line with population growth and regional development. As the center of activities, Yogyakarta City faces land limitations, leading to the expansion of residential areas into surrounding regions, including Ngemplak District, Sleman Regency. This study aims to analyze the suitability of residential land use in Ngemplak District with the Detailed Spatial Plan (RDTR) for the Sleman Timur Area. The analysis compares the pattern of residential development with the designated zoning in the RDTR. The results indicate that the proportion of residential areas complying with the RDTR increased from 31.02% in 2014 to 31,81% in 2024, reflecting more effective spatial planning. However, 2.32% of residential areas in 2024 remain inconsistent with land-use designations. The implementation of the RDTR has proven effective in controlling residential development, yet further monitoring is required to ensure sustainable land use.